Finger counting method is more accurate than age‐based weight estimation formulae in estimating the weight of Hong Kong children presenting to the emergency department. (21st September 2016) - So, Jerome LT; Chow, Eric PF; Cattermole, Giles N; Graham, Colin A; Rainer, Timothy H
Abstract: Objective: The aim of the present study was to evaluate the finger counting method and compare its performance with four commonly used age‐based weight estimation formulae in children aged 1–9 years presenting to the ED in Hong Kong. Methods: A cross‐sectional, observational study of children aged 1–9 years who presented to the ED of a tertiary referral hospital in Hong Kong over a 6 month period was conducted. Actual weight was compared with estimated weight using the finger counting method and four commonly used age‐based weight estimation formulae. Bland–Altman analysis was performed to evaluate the degree of agreement in which the mean percentage difference (MPD) and 95% limits of agreement (LOA) were calculated. Root mean squared error (RMSE) and proportions of weight estimates within 10%, 15% and 20% of actual weight were determined. Results: A total of 4178 children were included. The finger counting method was the most accurate method (MPD 0.1%; 95% LOA −34.0% to 34.2%). The original Advanced Paediatric Life Support (APLS) formula (MPD −7.0%; 95% LOA −38.4% to 24.3%) and the updated APLS formula (MPD −0.4%; 95% LOA −38.5% to 37.8%) underestimated weight whereas the Luscombe formula (MPD 7.2%; 95% LOA −31.8% to 46.2%) and the Best Guess formula (MPD 10.6%; 95% LOA −27.3% to 48.4%) overestimated weight. The finger counting method had smallest RMSE of 4.06 kg and estimated the largest proportion of children within 10%, 15% and 20% of actual weight. Conclusion: The finger counting method outperforms the commonly used age‐based weight estimation formulae in children aged 1–9 years presenting to the ED in Hong Kong.